Integration and Innovation: An Overview of the Development Status and Trends of Chinese Tea E-commerce Live Streaming - Xie, Ling; Nallaluthan, Kesavan (International Journal of Global Economics and Management, 2024)
As the level of technology in China continues to improve, e-commerce platforms are constantly evolving in practice and penetrating various industries, even covering all aspects of public life. The advantages of online shopping have had varying degrees of impact on the physical economy, with the traditional tea industry, which primarily relies on offline sales channels, being more severely affected. The large-scale introduction of tea and the obstruction of offline sales channels have made online business a breakthrough point for the tea industry. Many tea enterprises engage in online trade through live streaming e-commerce. This paper first analyzes the opportunities live streaming e-commerce brings to the tea industry and objectively explains the impact of live streaming e-commerce in conjunction with the characteristics of the tea industry. In the future, with the continuous expansion of the market and the rise of young consumers, tea e-commerce live streaming will focus more on product innovation, online and offline integration, and brand building, promoting the entire industry towards higher quality development.